Secondary adrenocortical insufficiency after treatment with retifanlimab: a case report - Zhang, Wenjing; Xiao, Li; Zhou, Guangxin; Zhu, Huijuan; Bi, Yongmin; Du, Junjie; Zhang, Da (Frontiers in Immunology, 2024)
With advancements in medical oncology, immune checkpoint inhibitors (ICIs) have become the first-line treatment for many malignancies. ICIs play a significant role in improving cancer prognosis, but a series of immune-related adverse events (irAEs), including immune-related endocrine events (irEEs), caused by ICIs have also aroused concerns. Rapid clinical identification of irAEs caused by ICIs is particularly important. We describe a case of secondary adrenocortical insufficiency (AI) after PD-1 treatment in a postoperative patient with endometrial cancer. A 73-year-old female patient developed anorexia, nausea, vomiting, malaise, electrolyte disturbances, ineffective symptomatic treatment, and decreased serum adrenocorticotropin and cortisol levels six months after retifanlimab treatment. The vomiting resolved, and the electrolyte levels were corrected after 3 days of treatment with glucocorticoids (hydrocortisone, intravenous, 200 mg/day). When patients present with gastrointestinal symptoms, such as poor appetite and nausea, not only symptomatic treatment but also a search for the etiology behind the symptoms is needed, especially in immunotherapy patients who should undergo a thorough evaluation of the endocrine system and be alert for adrenocortical insufficiency.